2023
DOI: 10.1002/jsfa.12814
|View full text |Cite
|
Sign up to set email alerts
|

Poly‐γ‐glutamic acid improved biological nitrogen fixation, water‐nitrogen productivity, and nitrate residue in cotton/soybean intercropping

Bo Jing,
Wenjuan Shi,
Lu Liu
et al.

Abstract: BackgroundPoly‐γ‐glutamic acid (γ‐PGA) can promote crop growth and improve soil properties efficiently. However, the optimal application rate of γ‐PGA in legume/non‐legume intercropping systems is still unclear. A potted experiment was conducted to investigate the effects of five γ‐PGA rates (0%, 0.1%, 0.2%, 0.3%, and 0.4%, represented by CK, P1, P2, P3, and P4, respectively) on biological nitrogen (N) fixation (BNF), water‐N productivity, and nitrate distribution in a cotton/soybean intercropping system.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
(126 reference statements)
0
2
0
Order By: Relevance
“…The results of our previous investigation demonstrated that the γ-PGA application of 0.22% in potted conditions can improve WUE. 51 In addition, the optimal γ-PGA application level for improving WUE and cotton yield obtained in cotton fields was 80 kg ha −1 . 16 Nevertheless, the impact of γ-PGA on soil improvement is intricately linked to variations in soil texture, climatic conditions, and application method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of our previous investigation demonstrated that the γ-PGA application of 0.22% in potted conditions can improve WUE. 51 In addition, the optimal γ-PGA application level for improving WUE and cotton yield obtained in cotton fields was 80 kg ha −1 . 16 Nevertheless, the impact of γ-PGA on soil improvement is intricately linked to variations in soil texture, climatic conditions, and application method.…”
Section: Discussionmentioning
confidence: 99%
“…19 Poly-γ-glutamic acid also promotes crop root growth, leading to increased root deposition in the soil. 51 Roots and their associated fungi, such as ectomycorrhizal species, intricately intertwine to create a network that effectively binds fine soil particles together, resulting in the formation of robust aggregates. 52 In this study, the soil water content in the 0-60 cm soil layer was increased significantly by the application of γ-PGA.…”
Section: Discussionmentioning
confidence: 99%